Återbesök till öppenvårdspsykiatrin i Bosnien-Hercegovina - Lagerkvist, Bengt; Jacobsson, Lars; Music, Emina (Socialmedicinsk tidskrift, 2009)
Författarna kan under en psykiatrikongress anekdotiskt utvärdera en sjuårig biståndsinsats till Bosnien-Hercegovina som blev en väsentlig del av landets mentalhälsovårdsreform efter kriget. Den etablerade öppenvårdspsykiatrin kom att stå som modell för utvecklingen i sydöstra Europa. Utbyggnaden av öppenvårdspsykiatrin i Bosnien Hercegovina är ett exempel på en framgångsrik psykiatrireform och är unik i sitt slag i sydöstra Europa. Ett femtiotal svenska experter deltog genom åren och flera landsting stödde verksamheten. In the aftermath of the war the authors were during seven years active in Swedish support with 3,5 million € to Bosnia and Herzegovina. Focus was on the mental health reform. The establishment of community mental health centres all over the country became a successful unique organisation. It has served as a model for seven other countries in South East Europe. The Swedish support encompassed training of more than 1500 health professionals such as psychiatrists, nurses, psychologists and social workers during courses and weekend seminars. A major task was changing of attitudes towards community psychiatry. An evaluation from year 2002 showed that about 5000 clients visited the 38 operating community mental health centres during one week or an average of 26 clients a day. Staffing consisted mostly of one doctor and three nurses doing home visits full time and psychologist and social worker part time for a catchment area of 65 000 inhabitants. More than 60% of the clients came for psychiatric problems with schizophrenia, depression and PTSD as dominating problem. Children had mostly a non psychiatric diagnoses and about 14% of the visits were health checks for certificates etc.The later results of the reform were confirmed at a psychiatric conference in Sarajevo, October 2007, but a final evaluation of the Swedish support is unfortunately not carried out.